Cultural Capital in Community Forestry Management for Forest Sustainable Utilities: A Case Study at Pa-Sakae Community, Tumbol E-pum, Amphur Dansai, Loei Province - Sakham, Phatcharaporn; Apichatvullop, Yaowalak (Journal of Mekong Societies, 2013)
This article is aimed at studying the cultural capital components of a Thai-Laos border community and analyzing the process of transforming these components into mechanisms of community-based forest management. The study found that in the past the Pa Sakae community was surrounded by rich natural resources and a good environment and utilized forest resources for their main livelihoods. In the present, however, the environment and natural resources have become highly degraded because of over-harvesting and forest encroachment, which transformed vast amounts of land into mono-cropping, especially in Para rubber and maize. Therefore, the cultural capital components have become an important tool in this community-based forest management process. These kinds of cultural capital are derived from two types of traditions: 1) the internal traditions such as the belief in ancestors’ spirits, practiced through rituals called ‘leang ban,’, ‘pa dong hor’ or sacred forest, as well as other kinds of wisdom or knowledge, and 2) traditions adopted from the outside, such as the relationship systems and social networks which have been adjusted and reproduced the values to become cultural capital to strengthen and empower community-based forest management. Consequently, these kinds of cultural capital have been transformed into four components of community-based forest management: forest utilization, rules and regulations, community organizations, and external supports. The community at Pa Sakae has developed their own cultural mechanisms that can be used as tools in community-based forest management through traditional forest management systems. These include local traditional cultures along with the recently developed management systems for more effectiveness and efficiency in community-based sustainable forest management.